2021
DOI: 10.3390/cancers13164116
|View full text |Cite
|
Sign up to set email alerts
|

Nature or Nurture? Role of the Bone Marrow Microenvironment in the Genesis and Maintenance of Myelodysplastic Syndromes

Abstract: Myelodysplastic syndrome (MDS) are clonal haematopoietic stem cell (HSC) disorders driven by a complex combination(s) of changes within the genome that result in heterogeneity in both clinical phenotype and disease outcomes. MDS is among the most common of the haematological cancers and its incidence markedly increases with age. Currently available treatments have limited success, with <5% of patients undergoing allogeneic HSC transplantation, a procedure that offers the only possible cure. Critical contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 187 publications
(224 reference statements)
1
10
0
Order By: Relevance
“…The contribution of human MDS-derived BM-MSCs for the engraftment and maintenance of MDS HSCs in mice was also corroborated in a recent study by Mian et al. ( 69 ). The authors injected patient derived HSCs into gelatin-based scaffolds that were previously seeded with autologous or allogeneic MDS-derived BM-MSCs and the construct was subsequently transplanted in mice.…”
Section: Properties Of Ex Vivo Expanded Mds-derive...supporting
confidence: 62%
“…The contribution of human MDS-derived BM-MSCs for the engraftment and maintenance of MDS HSCs in mice was also corroborated in a recent study by Mian et al. ( 69 ). The authors injected patient derived HSCs into gelatin-based scaffolds that were previously seeded with autologous or allogeneic MDS-derived BM-MSCs and the construct was subsequently transplanted in mice.…”
Section: Properties Of Ex Vivo Expanded Mds-derive...supporting
confidence: 62%
“…Yet, many issues are still unresolved. First, it remains unknown to what extent cell extrinsic ('niche') factors contribute to disease development, as has for instance been implicated in SDS, MDS, and MPN [63,[66][67][68][69]. Second, although excessive oxidative damage, UPR and ER stress responses and ribosomal dysfunction have all been implicated in the development of neutropenia, that these represent targetable vulnerabilities is still modest.…”
Section: Discussionmentioning
confidence: 99%
“…Although not the focus of this manuscript, alterations in the aged bone marrow microenvironment (e.g., in stromal and immune cells, cytokine/chemokine/extracellular matrix production and inflamm-aging) may lead to changes (e.g., of location, regulation, function) in HSPCs and support their evolution to hematological malignancies. The studies, which support these conclusions [ 19 , 250 , 273 , 274 , 275 , 276 , 277 ], are not reiterated here, except to highlight the controversy that surrounds the clonal origin of MDS MSC and MDS associated gene mutations or chromosomal rearrangements in MSCs that contribute to MDS progression, and which are described in detail in recent reviews [ 250 , 278 , 279 ]. Initial experiments in mice demonstrated that disruption of hematopoiesis associated with progression to an MDS-like disorder (characterized by anemia, thrombocytopenia, reduced B lymphoid cells and increased myeloid cells) occurred when the Dicer1 gene was deleted in murine osteoprogenitor cells [ 280 ].…”
Section: Shifting Human Hsc Heterogeneity With Aging and Clonal Hemat...mentioning
confidence: 98%